Effectiveness of using teaching strategies to engage adult male students who had previously experienced childhood difficulties in learning mathematics - Hasan, Abeer Abdulla (Curtin University, 2013)
The effectiveness of teaching strategies that engage adults was investigated for male college students who had experienced childhood difficulties in learning mathematics in the United Arab Emirates. The strategies were highly successful in terms of the nature of the classroom learning environment and students’ satisfaction. Qualitative methods clarified how these activities changed the learning environment in ways that were perceived to be beneficial by these students.